State of the art and challenges of security SLA for cloud computing. (April 2017) - Carvalho, Carlos André Batista de; Andrade, Rossana Maria de Castro; Castro, Miguel Franklin de; Coutinho, Emanuel Ferreira; Agoulmine, Nazim
Highlights: A classification of security SLAs solutions is presented. The security issues for SLA management in cloud computing environment are discussed. The research opportunities to develop a SLA for cloud security are enumerated. Graphical abstract: Abstract: There are users and organizations that resist adopting cloud computing solutions, due to concerns about the security and privacy of their data. A Service Level Agreement (SLA) can be used to address these concerns, increasing trust in the purchased services through the clear description of the guarantees offered by the provider to the subscribers. For this purpose, the authors performed a literature systematic mapping to enumerate existing solutions and open issues in security SLAs in cloud computing. This review is presented in this paper as well as an analysis of the state of art. This paper also presents a classification of the selected papers and a discussion about management of security SLAs in clouds.